Hepatoprotective Activity of Phyllanthus acidus L. Leaf Extract in Type 2 Diabetes Mellitus Mice - Oktaviona, Erin Eka Putri; Qomariyah, Nur; Khaleyla, Firas (LenteraBio : Berkala Ilmiah Biologi, 2023)
In patients with hyperglycemia and hypercholesterolemia, oxidative stress that causes hyperinsulinemia resulting in the formation of free radicals that can trigger inflammation and cell death in the liver. Reactive oxygen species (ROS) are free radicals that can damage tissues and are captured or neutralized by flavonoid compounds in P. acidus leaf that act as antioxidants. This study aims to examine the effect of P. acidus leaf extract in liver histopatology and Hepatosomatic Index (HSI) in a type 2 diabetes mellitus mice model. In this study, 24 male Deutsch Denken Yoken (DDY) strain mice were used, and divided into six treatment groups, namely the control group, the negative control group, the positive group, a dose of 215 mg/kg BW, a dose of 230 mg/kg BW, and a dose of 245 mg/kg BW. Data analysis with statistical tests. Liver histology scoring was calculated using the Kruskal-Wallis test (p<0.05) followed by the Mann-Whitney test. A one-way ANOVA test was performed for HSI data results (p<0.05) and resumed with Duncan’s test. The results of the research on the level of liver damage showed there was an effect of giving P. acidus leaf extract on the level of liver damage (p<0.05). In addition, the administration of P. acidus extract also affects the HSI value (p<0.05). Based on the results, it can be concluded that the dose 215 mg/kg BW of P. acidus leaf extract affected liver damage and Hepatosomatic Index (HSI).